TERRITORIAL ADMINISTRATION. PROBLEMS OF REFORMATION - A. Y. Manyushis (Финансы: теория и практика)
Article Retracted.The rational organization of a territory is one of the key factors in the effective social and economic development of countries in the post-industrial era. This is especially important for large countries such as Russia having the largest territory in the modern world community. It is noted that the economic levers of the local authorities’ influence on the regional development in general and particular companies and organizations are not sufficiently effective. The regional budget is the basic document that defines the development prospects of a region, but in the budget planning the interests of central departments dominate over regional interests. Regional resources are weakly dependent on the results of their activities. The incentives for employees involved in the implementation of the most effective solutions are insufficient or lacking. In this context, the following vital problems of the territorial administration reform (TA) in Russia are analyzed: the current stage specifics and the basic TA system requirements; principal shortcomings of the existing TA system; the TA object and functions; the distribution of competencies between the center and regions; the harmonization of interests of the center, regions, economic entities and citizens; factors of impact on the establishment of the new territorial organization in Russia; strategic policies for the development of the TA economic and organizational mechanisms. The approaches proposed thereto may be useful in the preparation of the concept and the forthcoming real work on the TA reform.